Burud Society and Bamboo Plants Utility : Dendrocalamus strictus - Deshmukh Pratap V; Pratap V (International Journal of Life Sciences, 2017)
Peoples from Burud society are economically poor and there is no any another source for livelihood. From their ancestors they weaves some things useful for daily needs from plant material like Lantana, Ipomoea, Shindi etc. After some working experience they leads for manufacture of articles from Bamboo. Some plants are very soft and some are very strong. Out of these plants one was bamboo which is very high and stem is strength. In our India Bamboo plants are distributed I Andhra Pradesh, Kerala, Karnataka, Himachal Pradesh, Maharashtra etc. This plant is very useful and maintains diversity of flora of region. No of peoples and their life style is depends on such plants because they got currency and job for daily maintenance. Dendrocalamus strictus Bamboo have no of uses to human being and also to environment.